Effect of nitrogen levels on growth and yield of turmeric - A D Warade, S K Attarde, B J Jadhao, R M Adpawar, (Journal of Spices and Aromatic Crops, 2003)
An experiment was conducted during 2000-2001 to study the response of two turmeric varieties (Krishna and Selam), five levels of nitrogen (0, 40, 80, 120, 150 kg ha-1) on growth and yield. The results indicated that variety Krishna responded favourably for all the characters to the application of 120 kg N ha-1. The maximum rhizome yield of 277.87 and 225.43 q ha-1, respectively was harvested by the application of 120 kg N ha-1 with turmeric variety ’Krishna’. The interaction of nitrogen x variety was significant only for fresh weight of fingers per plant.